2004
DOI: 10.1093/acprof:oso/9780199268436.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Challenges, Democratic Choices

Abstract: Most democratic citizens today are distrustful of politicians, political parties, and political institutions. Where once democracies expected an allegiant public, citizens now question the very pillars of representative democracy. This book documents the erosion of political support in virtually all advanced industrial democracies. Assembling a large array of cross-national public opinion data, this book traces the current challenges to democracy primary to changing citizen values and rising expectations. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,037 publications
(38 citation statements)
references
References 101 publications
1
26
0
6
Order By: Relevance
“…1 We argue that citizens' evaluations of the impartiality of institutions and public officials have a significant impact on evaluations of the performance of the political system as a whole (cf. Anderson et al 2005;Dalton 2004;Easton 1965Easton , 1975Norris 1999). Our theoretical and empirical claim is thus closely related to the argument behind the "procedural fairness" theory, that is, the willingness of citizens to defer to the decisions and rules created and implemented by public authorities and institutions depends on the fairness of the procedures through which these authorities exercise their authority (Tyler 2006).…”
Section: The Independent Variable: Perceptions Of Procedural (Un)fairmentioning
confidence: 75%
“…1 We argue that citizens' evaluations of the impartiality of institutions and public officials have a significant impact on evaluations of the performance of the political system as a whole (cf. Anderson et al 2005;Dalton 2004;Easton 1965Easton , 1975Norris 1999). Our theoretical and empirical claim is thus closely related to the argument behind the "procedural fairness" theory, that is, the willingness of citizens to defer to the decisions and rules created and implemented by public authorities and institutions depends on the fairness of the procedures through which these authorities exercise their authority (Tyler 2006).…”
Section: The Independent Variable: Perceptions Of Procedural (Un)fairmentioning
confidence: 75%
“…Berman (1997) argued that captious anger and hostility are endemic to what constitutes cynicism, and political cynics even have a pervasive disbelief in the possibility of good intentions of politicians. Recently, Dalton (2004Dalton ( , 2013 noticed a rise in political cynicism in Western societies. Furthermore, Pattyn, Van Hiel, Dhont, and Onraet (2012) showed that political cynics' skepticism towards politic(ian)s can be considered a potential hazard to democracy, as it is accompanied by lower governmental credibility and legitimacy, lower electoral and political participation, and increased support for extreme protest parties (B elanger & Aarts, 2006;Bergh, 2004).…”
Section: Integrating Old and New Alignmentsmentioning
confidence: 99%
“…Some political pundits attributed this success to ever increasing cynicism and anti-immigration attitudes. Indeed, public opinion and political debate have become polarized, leading many citizens to become cynical about politics and politicians (Dalton, 2004(Dalton, , 2013. At the same time, a rise of anti-immigration sentiment has been noticed (Pettigrew & Meertens, 1995;Semyonov, Raijman, & Gorodzeisky, 2006).…”
mentioning
confidence: 99%
“…Public confidence and support for democratic institutions is declining across established Western democracies (Dalton, 1999;Newton, 2006;Norris, 1999a). Documenting this decline across several countries, Russell Dalton (2004) notes that in Britain there has been general erosion in support of the party system and a decline in confidence expressed in the House of Commons. John Curtice and Roger Jowell (1995; demonstrate that in the UK voters are increasingly 'sceptical' about government and 'the ability of the system to respond to the demands of the citizenry' (1995, p. 167), concluding that 'Britain still appears to have low levels of confidence in both its political system and its politicians ' (1997, p. 107).…”
Section: The Decline In Public Confidence and Advocacy Democracy Reformsmentioning
confidence: 99%